2017
DOI: 10.1002/2016jd026292
|View full text |Cite
|
Sign up to set email alerts
|

Increasing heat waves and warm spells in India, observed from a multiaspect framework

Abstract: Recent heat waves have been a matter of serious concern for India because of potential impacts on agriculture, food security, and socioeconomic progress. This study examines the trends and variability in frequency, duration, and intensity of hot episodes during three time periods (1951–2013, 1981–2013 and 1998–2013) by defining heat waves based on the percentile of maximum, minimum, and mean temperatures. The study also explores heat waves and their relationships with hydroclimatic variables, such as rainfall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 86 publications
4
51
0
Order By: Relevance
“…Occurrences of compound events exceeding the P 10 /T 90 threshold during this period were shown for large regions of western Russia, implying severe conditions of this compound dry and hot event. Other regions with lower values of SCEI and different levels of occurrences included parts of India and northern China, where concurrent droughts and high temperature anomalies during summer 2010 have been shown in previous studies (Schubert et al 2014, Panda et al 2017. We also assessed other historical occurrences of compound dry and hot events and overall the two indicators performed well in identifying historical compound events (not shown).…”
Section: Monitoring Of Compound Dry and Hot Eventsmentioning
confidence: 84%
“…Occurrences of compound events exceeding the P 10 /T 90 threshold during this period were shown for large regions of western Russia, implying severe conditions of this compound dry and hot event. Other regions with lower values of SCEI and different levels of occurrences included parts of India and northern China, where concurrent droughts and high temperature anomalies during summer 2010 have been shown in previous studies (Schubert et al 2014, Panda et al 2017. We also assessed other historical occurrences of compound dry and hot events and overall the two indicators performed well in identifying historical compound events (not shown).…”
Section: Monitoring Of Compound Dry and Hot Eventsmentioning
confidence: 84%
“…Many parts of the world have witnessed an increased number of heatwaves in recent years (Rahmstorf and Coumou 2011, Sun et al 2014, Christidis et al 2015, including major global urban areas, where most of the world's human population now resides (Mishra et al 2015, Matthews et al 2017, and in India (Dash and Mamgain 2011, Rohini et al 2016, Panda et al 2017. In India, heatwaves during the pre-monsoon season (March−May) cover some area of the country nearly every year, cause high mortality, and affect a large population (Patz et al 2005, McMichael et al 2006, Hallegatte et al 2007, Dunne et al 2013, Pai et al 2013, Smith et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this increase, the frequency, magnitude, extent, and duration of extreme temperature events (heat waves, severe winter, hot [cold] days and nights) have also been increased over the last few decades (Mastrandrea et al, 2011;Donat et al, 2014;Lelieveld et al, 2016;Rahimi and Hejabi, 2017). In recent years, several studies have reported different temperature extremes across the globe; for example, the 2015 heat waves over Pakistan, India and 2003 heat waves over Europe and Russian (Cheng et al, 2012;Frías et al, 2012;Lau and Kim, 2012;Herring et al, 2015;Rahmstorf et al, 2016;Panda et al, 2017). These temperature extremes have adversely affected human well-being and resulted in extensive loss of agricultural production, biodiversity, hydropower generation, and food insecurity (Sen et al, 2007;Ashiq et al, 2010;Del Río et al, 2013;Abid and Ashfaq, 2016;Iqbal et al, 2016;Sen et al, 2016;Berardy and Chester, 2017).…”
mentioning
confidence: 99%